ECONOMIC DEVELOPMENT IN THE CONTEXT OF THE DICHOTOMY OF T. VEBLEN - Khomyn, Irina (Journal of European Economy, 2017)
The problem of analytical interpretation of indicators of economic development, which deals in international comparisons of their efforts in Ukraine was studied.